A new genus of Cranaidae from Ecuador (Opiliones: Laniatores) - Kury, Adriano B. (Zootaxa, 2012)
The new genus Zannicranaus is described from the Andes in central Ecuador based on two new species. It is characterizedby a guitar-shaped body, short sturdy pedipalpus, unique strong spiniform process in the frontal hump, sexually dimorphicbasichelicerite (very strong in male), an erect spine on the cheliceral bulla and paired ventral armature on male coxa IV.Zannicranaus monoclonius sp. nov., a species profusely colored in red, yellow and green, is described from ChimborazoProvince (Sibambe). Zannicranaus morlacus sp. nov., a dull-brown colored species, is the first reported harvestman from Azuay Province (Molleturo). The stylar caps, a novel structure, is described in the male genitalia of Cranaidae.